No more work : why full employment is a bad idea - Livingston, James, 1949- (The University of North Carolina Press, 2016)
For centuries we've believed that work was where you learned discipline, initiative, honesty, self-reliance--in a word, character. A job was also, and not incidentally, the source of your income: if you didn't work, you didn't eat, or else you were stealing from someone. If only you worked hard, you could earn your way and maybe even make something of yourself. In recent decades, through everyday experience, these beliefs have proven spectacularly false. In this book, James Livingston explains how and why Americans still cling to work as a solution rather than a problem--why it is that both liberals and conservatives announce that "full employment" is their goal when job creation is no longer a feasible solution for any problem, moral or economic. The result is a witty, stirring denunciation of the ways we think about why we labor, exhorting us to imagine a new way of finding meaning, character, and sustenance beyond our workaday world--and showing us that we can afford to leave that world behind.